2018
DOI: 10.1200/jco.2017.76.0876
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden in the First Year After Cancer Diagnosis: An Analysis of Patient-Reported Outcomes

Abstract: Purpose Improvement in the quality of life of patients with cancer requires attention to symptom burden across the continuum of care, with the use of patient-reported outcomes key to achieving optimal care. Yet there have been few studies that have examined symptoms in the early postdiagnosis period during which suboptimal symptom control may be common. A comprehensive analysis of temporal trends and risk factors for symptom burden in newly diagnosed patients with cancer is essential to guide supportive care s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 62 publications
12
124
4
Order By: Relevance
“…This is partially similar to our results. Our data did not confirm Bubis' et al (2018) results who found a significantly higher probability of reporting elevated scores in symptom burden within females and younger patients, in a population‐based cohort of newly diagnosed patients, regardless of cancer sites.…”
Section: Discussioncontrasting
confidence: 99%
“…This is partially similar to our results. Our data did not confirm Bubis' et al (2018) results who found a significantly higher probability of reporting elevated scores in symptom burden within females and younger patients, in a population‐based cohort of newly diagnosed patients, regardless of cancer sites.…”
Section: Discussioncontrasting
confidence: 99%
“…Online Resources 4 and 5 indicated that tumor site and gender might be associated with patients' burden. In all, women had better POS scores but reported higher values for anxiety and fatigue than male patients which confirms results identified in other studies and underlines the need for a closer look at gender differences in future studies [28][29][30].…”
Section: Assessed For Eligibility (N=3155)supporting
confidence: 88%
“…It fills a gap in the NETs literature regarding PROs. The symptoms most commonly scored moderate‐to‐severe are similar to other types of cancers . However, the symptom trajectory in NETs differs: whereas the odds of high scores decrease with each successive month from diagnosis time in other cancers, the proportion of elevated scores for NETs remains stable over 5 years following diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…In order to use this information to design patient support strategies, patient and disease factors associated with the report of moderate-to-severe scores were examined. The association of younger age with higher symptom burden has been reported in patients with cancer, albeit inconsistently [14,15,28]. The impact of comorbidity burden on symptoms is also common to other diseases [29,30].…”
Section: Discussionmentioning
confidence: 99%